(untitled) (Research, Society and Development, 2021)
Supernumerary teeth (ST) are changes of the dental development classified as a number anomaly, the most common reported in the dental clinics. This article aims to review in literature and to report through a clinical case the stages of the surgical procedure, relevant information on the diagnosis and treatment of supernumerary teeth as well. Patient E.D.L., a male one, 20 years old, attended the Polyclinic of Patos de Minas MG College, and the main complaint was the nuisance with supernumerary teeth in a total of ten elements. The work was submitted to the Research Ethics Committe (REC) with human beings from Faculdade Patos de Minas (FPM) under the number of opinion: 4,473,826. Anamnesis was performed, followed by a photographic protocol, asepsis, antisepsis and local anesthesia. A sulcular incision was made with detachment of the periosteum, followed by dislocation with straight and curved levers and forceps to remove occlusion teeth, the curettage of the alveolus with Lucas curette and irrigation with sterile saline. It was necessary to have an odonto-section with a Zecria drill on the included teeth. The flap was positioned and sutured with nylon suture. Ten days were waited for the suture to be removed. After conclusive diagnosis and surgical determination, the reported patient received treatment indicated for his case successfully, by removing his supernumerary teeth and guaranteeing his oral health, demonstrating the relevance of rapid and complet diagnosis, and also the individualization of propaedeutics in these cases, in order to avoid future complications and to improve the patient’s self-esteem and socialization.